A 3D Bioprinted in vitro Model of Neuroblastoma Recapitulates Dynamic Tumor‐Endothelial Cell Interactions Contributing to Solid Tumor Aggressive Behavior (Adv. Sci. 23/2022). Issue 23 (15th August 2022) - Ning, Liqun; Shim, Jenny; Tomov, Martin L.; Liu, Rui; Mehta, Riya; Mingee, Andrew; Hwang, Boeun; Jin, Linqi; Mantalaris, Athanasios; Xu, Chunhui; Mahmoudi, Morteza; Goldsmith, Kelly C.; et al.
Abstract : 3D Bioprinted in vitro Model of Neuroblastoma Neuroblastoma (NB) accounts for 50% of all cancers in infants with substantial mortality. Due to the lack of robust experimental models, the role of NB microenvironment in tumor progression is poorly understood. Through integrating 3D bioprinting and NB spheroid technologies, in article number 2200244, Kelly C. Goldsmith, Vahid Serpooshan, and co‐workers create an in vitro vascular model of NB and examine the tumor function within an endothelialized microenvironment.